2019
DOI: 10.5539/gjhs.v11n12p165
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Implications of Mental Health Stigma: Primary Health Care Providers’ Perspectives

Abstract: Stigma towards mental illness is a widespread phenomenon not just in the developing world, but also in developed countries. Unfortunately, this stigma is not only restricted to the general population, but is also prevalent among professional health care providers. Research from developing countries is scarce. Thus, the aim of this paper was to explore health care providers’ attitudes toward mental illness stigma in the primary health care settings. The review sheds light on the ethical implications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In our study, we are speculating that the results were similar because the majority of the students did not take the psychiatric nursing class. Health care providers, who did not receive sufficient education and had fewer interactions with people with mental illnesses, showed negative attitudes toward mental illnesses (Abuhammad & Dalky, 2019). In accordance with this, Mårtensson et al (2014) found out that nurses who have friends with mental illnesses had more positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we are speculating that the results were similar because the majority of the students did not take the psychiatric nursing class. Health care providers, who did not receive sufficient education and had fewer interactions with people with mental illnesses, showed negative attitudes toward mental illnesses (Abuhammad & Dalky, 2019). In accordance with this, Mårtensson et al (2014) found out that nurses who have friends with mental illnesses had more positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Attitude is defined as a "relatively enduring and general evaluation of an object, person, group, issue, or concept on a dimension ranging from negative to positive" (American Psychological Association [APA], n.d.a). Health workers' attitudes toward people with mental illnesses are similar to those of the general public (Abuhammad & Dalky, 2019;Tungchama et al, 2019). Therefore, health workers' attitudes and behaviors toward people with mental illnesses are reflected in the healthcare service they provide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for MNSDs in developing world youth is justified by the large and growing vulnerable population of C&A in LMICs, the high prevalence of untreated or badly treated MNSDs in this cohort [26], the unjust stigmatization and cruel treatment of individuals suffering from these disorders [27][28][29], and the existence and availability of promising treatments for MNSDs [30,31]. Screening procedures are overwhelmingly recognized as some of the most cost-effective preventive population-wide public health strategies for reducing societal burden and costs related to disease and disability [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%